2010
DOI: 10.1016/j.vetpar.2010.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of parasites in soil and dog feces according to diagnostic tests

Abstract: The objective of this study was to determine the prevalence of parasites in soil and dog feces according to diagnostic tests. We studied soil from 25 public squares in Seropédica, Brazil. Five samples of soil were collected from each square. Eighty-one fresh fecal samples from dogs were analyzed. The technique described by Dunsmore et al. and an adaptation of the Rugai et al. method were used to recover parasites in soil, and the Willis, Hoffman and Centrifugal-Flotation techniques were used to detect parasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
43
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 16 publications
6
43
2
2
Order By: Relevance
“…In this study, soil samples were analyzed using the flotation technique according to DADA (1979) 9 with sodium dichromate (d = 1.35) and zinc sulphate (d = 1.20) for helminth eggs and the modified Baermann method for larvae recovered according to RUGAI et al (1954) 38 . Although the methods used to recover zoonotic parasites in soil are not standardized and are not always comparable 23,26 , the techniques used in our study are in agreement with others studies and they are considered effective 16,21,23,28 . Another important aspect in parasite detection is the type of soil 21,22,23,26,41 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this study, soil samples were analyzed using the flotation technique according to DADA (1979) 9 with sodium dichromate (d = 1.35) and zinc sulphate (d = 1.20) for helminth eggs and the modified Baermann method for larvae recovered according to RUGAI et al (1954) 38 . Although the methods used to recover zoonotic parasites in soil are not standardized and are not always comparable 23,26 , the techniques used in our study are in agreement with others studies and they are considered effective 16,21,23,28 . Another important aspect in parasite detection is the type of soil 21,22,23,26,41 .…”
Section: Discussionsupporting
confidence: 86%
“…Although the methods used to recover zoonotic parasites in soil are not standardized and are not always comparable 23,26 , the techniques used in our study are in agreement with others studies and they are considered effective 16,21,23,28 . Another important aspect in parasite detection is the type of soil 21,22,23,26,41 . In this study, we observed that soil from all studied place and squares were primarily composed of sand, and more rarely clay soil.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…eggs (70.6 -87.5 µm in length by 31.9 -41.2 µm in diameter), found in 31 samples in this study, were compatible with T. vulpis, suggesting that these positive samples were from dogs. The frequency of this agent was higher than those reported in recent studies performed in public areas in Brazil 8,10 .…”
Section: Discussioncontrasting
confidence: 67%
“…Insofar as the inhabitants of the Ilha da Marambaia have the habit to defecate on the soil, this study suggests that a possible source of environmental contamination for the said parasite was probably humans infected with A. lumbricoides. Furthermore, MANDARINO-PEREIRA et al (2010) 10 described a similar scenario in the public areas of the state of Rio de Janeiro.…”
Section: Discussionmentioning
confidence: 86%